CYP17 genotype modifies the impact of anthropometric variation on salivary estradiol in healthy women. Issue 4 (2nd December 2014) - Rowe, Elizabeth; Van Horn, Andrew; Rockwell, L. Christie; Lewton, Kristi; Nalley, Thierra K.
ABSTRACT Several studies demonstrate that human ovarian function is responsive to the energetic environment, which has led to the development of theoretical models that explain this phenomenon. Although many genes are involved in ovarian hormone production, the possibility that genetic polymorphism may affect ovarian response to energetic conditions has not been considered. Cytochrome P450c17α is an enzyme that produces androgen precursors used to make estrogens during ovarian steroidogenesis, and is encoded by the CYP17 gene. A functionally significant variant within the promoter region of CYP17 has been linked to variation in steroid production, and some evidence suggests that this polymorphism could alter transcription of CYP17 in an insulin‐dependent manner. We tested the hypothesis that the CYP17 variant affected the relationship between anthropometric measurements and salivary estradiol in healthy women in the United States (n = 28). PCR‐RLFP analysis was used to genotype women for the genetic variant, and estradiol was assayed from saliva by EIA. Moderated regression analysis of these preliminary data revealed a significant interaction between waist‐to‐hip ratio and CYP17 genotype (P = 0.004). Our study provides evidence that gene–environment interactions should be considered in future adaptive models for human ovarian function. Moreover, our results stand to illuminate possible associations between this genetic variant and reproductive disease. Am J Phys Anthropol 156:665–670, 2015. © 2014 Wiley Periodicals, Inc.